Discrimination and classification of Eurycoma longifolia Jack in medicinal foods by means of a DSP-based electronic taste sensor - M. Z., Abdullah; A.S.A., Rahman; Ali Yeon, Md Shakaff; Mohd Noor, Ahmad (SAGE Publications, 2009)
Link to publisher's homepage at http://tim.sagepub.com/